Green awareness and green product: A direction for sustainable consumption - Butar Butar, Senita; Ambarita, Nita; Haniva, Respita (Applied Environmental Science, 2024)
Various parties are trying to prevent and overcome this problem in various ways. People are beginning to receive news, invites, education, and ads to raise their awareness of environmental sustainability. Consumers are becoming more conscious of the damaging effects that their purchases have on the environment. With green awareness increasing among consumers, they take steps to support the sustainability of the environment, one way is to use environmentally friendly products or green products. This study aims to find out how trends in research on how green awareness encourage consumer interest in buying and using green products. Descriptive bibliometric analysis is the research methodology employed. The Scopus database was utilized by researchers to locate data. Through four refinement procedures (identification, screening, eligibility assessment, and inclusion), 102 publishing data were acquired. The VOS Viewer tool will be used to examine the data. Compared to previous years, 2022 has published the most articles (28 publications). Citation trends related to green awareness and green products occurred in 2016 with 456 citations. China is the most influential nation in this field, with 29 publications and 14 connections to international collaboration.  Research on Green Products and Green Awareness is centered on 1) consumption, green consumption, and manufacturer; 2) green purchase behavior, green purchase, and environmental knowledge; 3) policy maker, TPB, and perception.